Metabolomic Assay, Computational Screening, and Pharmacological Evaluation of Caulerpa racemosa as an Anti-obesity With Anti-aging by Altering Lipid Profile and Peroxisome Proliferator-Activated Receptor-γ Coactivator 1-α Levels - Permatasari, Happy Kurnia; Nurkolis, Fahrul; Hardinsyah, Hardinsyah; Taslim, Nurpudji Astuti; Sabrina, Nindy; Ibrahim, Faisal Maulana; Visnu, Jodi; Kumalawati, Dian Aruni; Febriana, Sri Awalia; Sudargo, Toto; Tanner, Melvin Junior; Kurniatanty, Isma; et al. (Frontiers in Nutrition, 2022)
Obesity is associated with an accelerated aging process which prevents a healthy aging. Both obesity and aging were manifested in peroxisome proliferator-activated receptor γ coactivator α (PGC-1α) level. These studies fulfill the scientific gap of ansambled pharmacological activity assay of C. racemosa done in previous preclinical trial. Six major compounds from Sea grapes (Caulerpa racemosa) extract were evaluated using an in silico approach against human pancreatic lipase, a-glucosidase, and a-amylase to predict prospective anti-obesity candidates. The lipase inhibitory activity of the extract reached 90.30 ± 0.40%, 1.75% lower than orlistat. The a-amylase inhibitory assay of the extract was 84.07 ± 5.28%, while inhibitory activity against a-glucosidase was 81.67 ± 1.54%; both were lower than acarbose. We observe the effect of C. racemosa extract as anti-obesity with anti-aging by evaluating the obesity parameters in human body for 4 weeks period. There were a significant decrease in blood glucose, total cholesterol, low-density lipoprotein (LDL), triglycerides (TG), waist circumference, WHR, Body Weight (p<0.05); PGC-1α and high-density lipoprotein (HDL) increased significantly (p=0.000), respectively, in group B compared to group A. Our study revealed that sea grapes extract is a potent anti-obesity with anti-aging reagent that does not produce any significant adverse effects.